New clues in the nucleus: transcriptional reprogramming in effector-triggered immunity - BHATTACHARJEE, SAIKAT; Garner, Christopher M.; Gassmann, Walter (Frontiers in Plant Science, 2013)
The robustness of plant effector-triggered immunity is correlated with massive alterations of the host transcriptome. Yet the molecular mechanisms that cause and underlie this reprogramming remain obscure. Here we will review recent advances in deciphering nuclear functions of plant immune receptors and of associated proteins. Important open questions remain, such as the identities of the primary transcription factors involved in control of effector-triggered immune responses, and indeed whether this can be generalized or whether particular effector-resistance protein interactions impinge on distinct sectors in the transcriptional response web. Multiple lines of evidence have implicated WRKY transcription factors at the core of responses to microbe-associated molecular patterns and in intersections with effector-triggered immunity. Recent findings from yeast two-hybrid studies suggest that members of the TCP transcription factor family are targets of several effectors from diverse pathogens. Additional transcription factor families that are directly or indirectly involved in effector-triggered immunity are likely to be identified.